IDENTIFIKASI TINGKAT PENGGUNAAN RUANG TERBUKA PUBLIK DI KOTA MAKASSAR, DI LIHAT DARI ASPEK AKTIVITAS, FASILITAS DAN KRITERIA PERANCANGAN - Andi Asmuliany (Teknosains, 2014)
The aim of the study was to describe the condition and utility of green open space as a public space in Makassar. The collection of data was done by a survey and interview. The data were analyzed by using expert judgement and likert scale. The result of the study indicate that object studied which has the highest utility is Losari beach with score 4,04. The utility of Losari beach as a public space is able to meet the need of the community according to its functions, namely as a sports area, playing ground, social interaction, socio-culture, and socio economic. The success of the utility of the beach is supported by its strategic location, design, beautiful scene, large area, sufficient capacity, and no divider so thet the community can use this area any time as an open common space to carry out various activities.